Una visión filogenética de Frankliniella (Tbysanoptera: Tbripidae) - Retana Salazar, Axel P (Universidad de Costa Rica, 1998)
The pbylogeny of the species groups of Franldiniella and the position of Exophtalmothirps and Bolbothrips are discussed with reference to recent literature and analysis with the cladistic software PAUP 3.0 in its heuristic option, the matrix has 24 taxa and 25 cbaracteristics for each; 1) the intonsa group is nOl a well defined taxon and may include groups of species, but there are no good morphological traits fot its recognition, 2) the pulchella and cephaUca groups are consistent monophyletic groups of species, 3) the minuta group is rnonophyletic with a few roorphological constraints, 4) Exophtalmothrips and Bolbothíips seem to he segregated, and notsynonymous of Franlcliniella.